Defining the environmental crime – why is the global legal and political action urgently needed - Bajrektarevic, Anis H (AEI Insights, 2021)
Preservation and protection of environment appears as one of the largest challenges of our time. It necessitates urgent but also comprehensive, planetary action. One of the key issues is to define a scope of future international instrument as well as its definition. This requires global political action which will then eventually translate into a coordinated legal action and finally articulate itself in viable international treaty. Institutional collaboration among stakeholders and agencies needs to be improved as much as the currently existing approaches need to be harmonized. Only an improved institutional framework between agencies and stakeholders that protects environment could enhance and accelerate cooperation to the levels equal to an environmental and climate change challenge. The very creation of such framework could also contribute to the harmonization of monitoring and reporting systems. It will also lead to more coordinated, more effective and properly financed policy instruments as well as more efficient legal enforcement on supranational, national and sub-national level.